Efficacy of intravenous tramadol and low-dose ketamine in the prevention of post-spinal anesthesia shivering following cesarean section: a double-blinded, randomized control trial - Lema GF; Gebremedhn EG; Gebregzi AH; Desta YT; Kassa AA (Dove Medical Press, 2017)
Girmay Fitiwi Lema,1 Endale Gebreegziabher Gebremedhn,1 Amare Hailekiros Gebregzi,1 Yilkal Tadesse Desta,1 Adugna Aregawi Kassa2 1Department of Anesthesia, School of Medicine, University of Gondar, Gondar, 2Department of Anesthesia, School of Medicine, Addis Ababa University, Black Lion Specialized Hospital, Addis Ababa, Ethiopia Background: Shivering is a frequent and undesirable complication of spinal anesthesia. It is a physiologic response to increase the body core temperature in an attempt to raise metabolic heat production. However, shivering may trigger myocardial ischemia; increase intraocular and intracranial pressures, increase wound pain, delay wound healing and interfere with pulse rate, blood pressure and electrocardiogram monitoring. We aimed to compare the efficacy of intravenous (IV) ketamine with IV tramadol for the prevention of shivering in patients who underwent cesarean delivery under spinal anesthesia. Patients and methods: A prospective, randomized, double-blind study was conducted. One hundred and twenty-three American Society of Anesthesiologist I and II patients, aged between 18 and 39 years, who underwent cesarean section were included in the study. Patients were randomly allocated to one of three groups: group S (n=41; control group) received saline, group K (n=41) received ketamine 0.2 mg/kg and group T (n=41) received tramadol 0.5 mg/kg. Incidence and grade of shivering and side effects between the treatment groups were recorded.Results: The incidence of shivering was significantly reduced in the ketamine and tramadol groups (41.5% and 53.7%, respectively) compared to the saline group (70.7%; p=0.028). Grade 3 shivering occurred in 16 (39%) patients in the saline group, compared to 9 (22%) in the tramadol group and 8 (19.5%) in the ketamine group (p=0.011). Only two cases in the saline group developed grade 4 shivering (p<0.01). Neonatal outcome and perioperative complications were comparable among the three groups. Conclusion: The prophylactic administration of low-dose IV ketamine or IV tramadol is effective for reducing the incidence and intensity of shivering. We recommend low-dose IV ketamine or tramadol prophylaxis for parturients undergoing cesarean section under spinal anesthesia. Keywords: cesarean delivery, spinal anesthesia, shivering, prophylaxis, ketamine, tramadol, efficacy